A circulação do conhecimento pedagógico anarquista entre Brasil e Portugal (1900 a 1930) - Oliveira, Francisco Robson Alves de (2019)
This thesis investigates the circulation of the anarchist pedagogical knowledge between Brazil and Portugal, from the 1900s to the 1930s. This study has, as its reflection field, therefore, the Libertarian Education, and inserts itself in the vast group of researches about social movements, aiming to contribute with new elements to the Popular Education History in Brazil and in Portugal. Its core lies in studying how the anarchist pedagogical knowledge circulated and how its practices were exchanged, specifically on the circuit Brazil- Portugal-Brazil, using as a starting point the exam of the Libertarian Education practices debated in the libertarian press, in the various anarchist editorial projects and in the permanent flow of militants between the two countries. This work also tried to understand the Education concepts debated via anarchist press, in the many social places of the libertarian educational experience (such as the libertarian Schools, the Culture and Social Studies Centers, Athenaeums and Libraries) and in the diverse social practices linked to the anarchist educational spaces and associative ones (like the courses, conferences, and the "commented lectures"). The methodology of this research has its bases in the social history and in the compared perspective in education, referring itself as a qualitative base study, favoring the analysis of the multi-directional webs of discourses about education, with a particular immersion over the laborer press, contained in its periodicals, books, memoirs and letters between militants of the two countries. This investigation provided the reexamination and recovery of part of the bibliography concerning the History of the Libertarian Education, due to this educational perspective’s presence in the laborer and anarchist press, as well as helped understand part of the yearnings and the projects conceived by this libertarian and educational militancy in Brazil and in Portugal, from the letters exchanged between militants of these countries.